(untitled) (Research, Society and Development, 2022)
A comparative study was carried out with the partial replacement of Triticum durum semolina in fettuccine pasta with bamboo fiber (BF) and young bamboo culm flour (YBCF) regarding the consumer demand for healthier products and the inconvenience of using wheat bran in whole-grain pasta. Through a 2² central rotation composite design (CCRD), with five trials at the central point, totalling 13 essays (P1-P13) with independent variables X (0% to 3.5% of BF) and Y (YBCF) (0% to 3.5% of semolina substitution). There was no significant effect of the variables on optimal cooking time (OCT), mass gain (MG), volume increase (VI), loss of soluble solids (LSS), and force to cut of samples, although there was an increase in the color parameters L* and a*. Pasta P7, P8, and P10 showed average scores in sensory analysis within the region of acceptance as a control pasta. Therefore, it was possible to use YBCF in pasta production, suggesting a balance in managing bamboo clumps.